Cross-document Event Coreference Resolution based on Cross-media Features - Zhang, Tongtao; Li, Hongzhi; Ji, Heng; Chang, Shih-Fu (Proceedings of the 2015 Conference on Empirical Methods in Natural Language Processing, 2015)
In this paper we focus on a new problem of event coreference resolution across television news videos. Based on the observation that the contents from multiple data modalities are complementary, we develop a novel approach to jointly encode effective features from both closed captions and video key frames. Experiment results demonstrate that visual features provided 7.2% absolute F-score gain on state-of-the-art text based event extraction and coreference resolution.